Intraseasonal Drivers of the 2018 Drought Over São Paulo, Brazil - Gozzo, Luiz Felippe; Drumond, Anita; Pampuch, Luana Albertani; Ambrizzi, Tércio; Crespo, Natália Machado; Reboita, Michelle Simões; Bier, Anderson Augusto; Carpenedo, Camila Bertoletti; Bueno, Paola Gimenes; Pinheiro, Henri Rossi; Custodio, Maria de Souza; Kuki, Cassia Akemi Castro; et al. (Frontiers in Climate, 2022)
Dry conditions occurred over São Paulo state (southeastern Brazil) from February to July 2018, causing the driest semester in thirty-five years. Socioeconomic impacts included a record number of fire spots, most adverse conditions to pollutant dispersion in three years and the winter's lowest water reservoirs stored volume in seventeen years. This paper discusses climate drivers to the onset and persistence of the dry conditions, with special attention to the intraseasonal forcing. Barotropic atmospheric circulations forced by the intraseasonal Pacific-South America teleconnection pattern, embedded in the lower frequency setup of the Pacific Decadal Oscillation and the Atlantic Multidecadal Oscillation, were identified as main large-scale forcings to reduce precipitation. Drought evolution was modulated by other intraseasonal drivers such as the Madden Julian, Antarctic and 10-30 days Oscillations. A break in the six-month dry condition, in March 2018, highlighted the important role of such oscillations in determining precipitation anomalies over SP. Results show that intraseasonal phenomena and their interactions control drought characteristics such as magnitude, persistence and spatial distribution within a setup determined by lower-frequency oscillations. The intraseasonal timescale seems to be key and must be considered for a complete description and understanding of the complex drought evolution process in São Paulo.